2016
DOI: 10.1186/s13071-016-1634-y
|View full text |Cite
|
Sign up to set email alerts
|

Larval application of sodium channel homologous dsRNA restores pyrethroid insecticide susceptibility in a resistant adult mosquito population

Abstract: BackgroundMosquitoes host and pass on to humans a variety of disease-causing pathogens such as infectious viruses and other parasitic microorganisms. The emergence and spread of insecticide resistance is threatening the effectiveness of current control measures for common mosquito vector borne diseases, such as malaria, dengue and Zika. Therefore, the emerging resistance to the widely used pyrethroid insecticides is an alarming problem for public health. Herein we demonstrated the use of RNA interference (RNAi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 53 publications
1
33
0
Order By: Relevance
“…To our knowledge, this is the first study to demonstrate the susceptibility status of A. aegypti against different registered pyrethroids in Tanzania and there are limited data to compare our findings with. In other countries, studies have found detailed mechanisms that are involved in the different insecticides resistance, which is also needed to be done in Tanzania for strategic control of A. aegypti as in Thailand and Brazil [33, 34]. …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to demonstrate the susceptibility status of A. aegypti against different registered pyrethroids in Tanzania and there are limited data to compare our findings with. In other countries, studies have found detailed mechanisms that are involved in the different insecticides resistance, which is also needed to be done in Tanzania for strategic control of A. aegypti as in Thailand and Brazil [33, 34]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the V1016G mutation has not been reported in Latin America [31,32,46,47]. Instead, mutation V1016I was found, and often coexists with F1534C in South and North America, such as Venezuela [48], three French overseas territories [49], Brazil [50,51,52], Mexico [53], and the USA [54]. More recently, V1016I and F1534C were detected in Ghana, Africa [55], and a new mutation, T1520I, was found along with the F1534C mutation in a population in India [56].…”
Section: Identification Of Single Nucleotide Polymorphisms (Snps) mentioning
confidence: 99%
“…So far, V1016G has been detected only in Southeast Asia [34,37,40,41,44,45], whereas V1016I is distributed in South and North America [48,49,50,51,52,53]. More recently, V1016G, along with F1534C, was also detected in Ghana.…”
Section: Evolution Of Kdr Mutations In Aedes Aegyptimentioning
confidence: 99%
“…Larvae are simple to target with eRNAi by ingestion as they eat steadily, volubly, and are generally less mobile than adults (hence can naturally take up dsRNA that is concentrated within local food sources). For aquatic larvae, dissolving dsRNA in solution and bathing the larvae within it, is the most common method of effecting gene silencing via eRNAi (Figueira-Mansur et al, 2013;Singh et al, 2013;Whyard et al, 2015;Bona et al, 2016). dsRNA can be delivered to non-aquatic larvae: (1) topically via droplet feeding (Toprak et al, 2013), (2) by inducing the larvae to feed upon dsRNA-expressing transgenic plants (Xiong et al, 2013;Mamta et al, 2015;Tian et al, 2015;Hu et al, 2016), (3) by feeding larvae dsRNA-expressing transgenic bacteria (Zhu et al, 2011;Yang & Han, 2014;Li et al, 2015c), and (4) by feeding larvae naked dsRNA overlaid onto an artificial diet (Asokan et al, 2014;Yang & Han, 2014;Hu et al, 2016).…”
Section: Ernai Delivery Methods: Larvaementioning
confidence: 99%
“…In this context, the development of new methods for insect control is of key importance and there has been intense interest in the utility of gene silencing methods induced by RNA interference (RNAi). RNAi can induce mortality (Yang & Han, ; Cao et al., ; Abd El Halim et al., ; Christiaens et al., ; Hu et al., ; Malik et al., ), create beneficial phenotypes for insect control (Salvemini et al., ; Shukla & Palli, ; Peng et al., ; Yu et al., ), and prevent pesticide resistance in insect pests (Figueira‐Mansur et al., ; Guo et al., ; Wei et al., ; Bona et al., ; Sandoval‐Mojica & Scharf, ). Therefore, the potential for RNAi as a basis for future pest management strategies holds great promise (Huvenne & Smagghe, ; Gu & Knipple, ; Scott et al., ; Baum & Roberts, ; Kim et al., ).…”
Section: Rnai and The Sterile Insect Technique (Sit)mentioning
confidence: 99%